A phenylpropanoid diglyceride associates with the leaf rust resistance Lr34res gene in wheat. (October 2020) - Rajagopalan, Nandhakishore; Lu, Yuping; Burton, Ian W.; Monteil-Rivera, Fanny; Halasz, Annamaria; Reimer, Elsa; Tweidt, Rebecca; Brûlé-Babel, Anita; Kutcher, Hadley R.; You, Frank M.; Cloutier, Sylvie; Cuperlovic-Culf, Miroslava; et al.
Abstract: The gene Lr34res is one of the most long-lasting sources of quantitative fungal resistance in wheat. It is shown to be effective against leaf, stem, and stripe rusts, as well as powdery mildew and spot blotch. Recent biochemical characterizations of the encoded ABC transporter have outlined a number of allocrites, including phospholipids and abscisic acid, consistent with the established general promiscuity of ABC transporters, but ultimately leaving its mechanism of rust resistance unclear. Working with flag leaves of Triticum aestivum L. variety 'Thatcher' (Tc) and a near-isogenic line of 'Thatcher' into which the Lr34res allele was introgressed (Tc+ Lr34res ; RL6058), a comparative semi-targeted metabolomics analysis of flavonoid-rich extracts revealed virtually identical profiles with the exception of one metabolite accumulating in Tc+ Lr34res, which was not present at comparable levels in Tc. Structural characterization of the purified metabolite revealed a phenylpropanoid diglyceride structure, 1- O - p -coumaroyl-3- O -feruloylglycerol (CFG). Additional profiling of CFG across a collection of near-isogenic lines and representative Lr34 haplotypes highlighted a broad association between the presence of Lr34res and elevated accumulations of CFG. Depletion of CFG upon infection, juxtaposed to its relatively lower anti-fungal activity, suggests CFG may serve as a storage form of the more potent anti-microbial hydroxycinnamic acids that are accessed during defense responses. Altogether these findings suggest a role for the encoded LR34res ABC transporter in modifying the accumulation of CFG, leading to increased accumulation of anti-fungal metabolites, essentially priming the wheat plant for defense. Graphical abstract: Image 1 Highlights: The Lr34res allele in wheat elicits durable resistance against rust pathogens. Metabolomics reveal accumulation of a phenylpropanoid diglyceride in Lr34res wheat. The phenylpropanoid diglyceride is depleted upon rust infection. The phenylpropanoid diglyceride has anti-fungal activity. Lr34res is associated with accumulation of an anti-fungal phenylpropanoid diglyceride.